The Effect of Combination of Porang Tuber Starch (Amorphophallus muelleri Blume) with Lactose on the Physical Properties of Bajakah Root (Spatholobus littoralis Hassk) Water Extract’s Tablet - Ermawati, Dian Eka; Tambunan, Rido Rohana; Darojati, Ulfa Afrinurfadhilah (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Kalimantan's people drink bajakah roots as a traditional medicine to restore stamina and treat various diseases. The infusion is less practical and unstable, so it was developed into a tablet. Porang is a local tuber that contains amylum and amylopectin. The combination of starch-lactose has been widely used as a tablet filler and produces tablets with good physical properties. This study aimed to determine the effect of the combination of porang starch-lactose on the granules and tablets' physical properties. Bajakah roots were infused and dried using a freeze-dryer. The antioxidant activity was measured using the DPPH method. Tablets of bajakah root water extract were made with a 1:1 porang tuber starch-lactose ratio using the dry granulation. Physical evaluations of granules and tablets were conducted, including flow rate, angle of repose of granules, and weight uniformity, hardness, friability, and disintegration time of tablets. Porang tubers-lactose with a ratio of 1:1 produced tablets with good evaluation results with a granule flow rate of 9.70±0.92 g/s and an angle of repose of 26.15±1.79°. Uniformity of tablet weight met acceptance value, with hardness of 5.38±0.90 Kg, friability of 0.26±0.05%, and disintegration of 10.60±1.33 min. Porang tuber fulfills the requirements of a good tablet filler and can be developed as a tablet filler.